ADVANCING QUALITY COMPETITION IN BIG DATA MARKETS. (4th March 2020) - Kuenzler, Adrian
Abstract: The European Commission in its decision in Google Search (Shopping) found that a dominant search engine abused its market power by giving preferential treatment to its own related services over those of rivals. Conventional market mechanisms, it is supposed, can no longer correct the harm arising from such conduct. But there is disagreement in legal scholarship as to what this harm actually represents. This article maintains that the practice of self-favouring is best understood as an attempt to ward off product quality degradations in digital markets, which are difficult to repair purely by means of the consumer's sole ability to switch. Framed against Albert Hirschman's well-known work on Exit, Voice, and Loyalty, the Commission's ruling must be understood as recognition that rivalry stemming from smaller market actors will not necessarily prevent large platforms from degrading product quality, despite the consumer's ability to gain access to a variety of services that are only a click away. The article explicates the market's functioning and the available methods of recuperation against the backdrop of the available case law in this area, and expounds the Commission's findings in light of Hirschman's theory.